Two Functional Copies of the DGCR6 Gene Are Present on Human Chromosome 22q11 Due to a Duplication of an Ancestral Locus - Edelmann, Lisa; Stankiewicz, Pavel; Spiteri, Elizabeth; Pandita, Raj K.; Shaffer, Lisa; Lupski, James; Morrow, Bernice E.

(untitled) (Genome Research, 2001)
The DGCR6 (DiGeorge critical region) gene encodes a putative protein with sequence similarity to gonadal(gdl), a Drosophila melanogaster gene of unknown function. We mapped the DGCR6 gene to chromosome 22q11 within a low copy repeat, termed sc11.1a, and identified a second copy of the gene, DGCR6L, within the duplicate locus, termed sc11.1b. Both sc11.1 repeats are deleted in most persons with velo-cardio-facial syndrome/DiGeorge syndrome (VCFS/DGS), and they map immediately adjacent and internal to the low copy repeats, termed LCR22, that mediate the deletions associated with VCFS/DGS. We sequenced genomic clones from both loci and determined that the putative initiator methionine is located further upstream than originally described, but in a position similar to the mouse and chicken orthologs.DGCR6L encodes a highly homologous, functional copy ofDGCR6, with some base changes rendering amino acid differences. Expression studies of the two genes indicate that both genes are widely expressed in fetal and adult tissues. Evolutionary studies using FISH mapping in several different species of ape combined with sequence analysis of DGCR6 in a number of different primate species indicate that the duplication is at least 12 million years old and may date back to before the divergence of Catarrhines from Platyrrhines, 35 mya. These data suggest that there has been selective evolutionary pressure toward the functional maintenance of both paralogs. Interestingly, a full-length HERV-K provirus integrated into the sc11.1a locus after the divergence of chimpanzees and humans.